2014
DOI: 10.1097/phm.0000000000000059
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Based Muscle Attenuation and Electrical Impedance Myography as Indicators of Trunk Muscle Strength Independent of Muscle Size in Older Adults

Abstract: Objective To examine the associations of computed tomography (CT) -based x-ray attenuation and paraspinal electrical impedance myography (EIM) measures of trunk muscles with absolute and relative (normalized by body weight) trunk extension strength, independent of muscle cross-sectional area (CSA). Design A cross-sectional study of mobility-limited community dwelling older adults (34 women, 15 men, mean age 78.2±7.2 years) recruited from within an existing prospective research cohort. Trunk extension strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
5
20
0
Order By: Relevance
“…Although most prior studies of muscle density and area have focused on thigh musculature, Goodpaster et al observed that trunk muscle density (our primary outcome) was strongly correlated with thigh density (r=0.65–0.77; p<0.01) [26]. Trunk muscle density has been correlated with trunk muscle strength across multiple muscle groups (r =0.32–0.61; p <0.05) [35]. Adults with moderate or severe back pain had lower trunk muscle density (by 3.4 HU) and poorer score in lower extremity performance tests (chair stands, timed pace walk, and timed standing balance) compared to healthy controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although most prior studies of muscle density and area have focused on thigh musculature, Goodpaster et al observed that trunk muscle density (our primary outcome) was strongly correlated with thigh density (r=0.65–0.77; p<0.01) [26]. Trunk muscle density has been correlated with trunk muscle strength across multiple muscle groups (r =0.32–0.61; p <0.05) [35]. Adults with moderate or severe back pain had lower trunk muscle density (by 3.4 HU) and poorer score in lower extremity performance tests (chair stands, timed pace walk, and timed standing balance) compared to healthy controls [36].…”
Section: Discussionmentioning
confidence: 99%
“…CT scans that identified the presence of moderate to severe central canal stenosis or severe neuroforaminal stenosis were included in this study. 17 …”
Section: Methodsmentioning
confidence: 99%
“…9, 23 Although imaging was not part of the primary aims of Boston RISE a separate ancillary study of Boston RISE was conducted by different authors among 51 participants and included CT scans of the lumbar spine that were used for this study. 24 Additional criteria for the current study included completion of measures of neuromuscular attributes and self-reported and performance-based mobility. On the basis of these criteria, of the 430 participants from the Boston RISE 50 participants met the inclusion criteria.…”
Section: Methodsmentioning
confidence: 99%